2009
DOI: 10.1038/nn.2384
|View full text |Cite
|
Sign up to set email alerts
|

Selective suppression of hippocampal ripples impairs spatial memory

Abstract: Sharp wave-ripple (SPW-R) complexes in the hippocampus-entorhinal cortex are believed to be important for transferring labile memories from the hippocampus to the neocortex for long-term storage. We found that selective elimination of SPW-Rs during post-training consolidation periods resulted in performance impairment in rats trained on a hippocampus-dependent spatial memory task. Our results provide evidence for a prominent role of hippocampal SPW-Rs in memory consolidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
1,137
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,315 publications
(1,192 citation statements)
references
References 14 publications
52
1,137
0
3
Order By: Relevance
“…Importantly, this replay seems to coincide with the sharp wave ripples that originate in the hippocampus and are characteristic of SWS. These have been shown to be important for spatial learning in rats, with disruption of sharp wave ripples resulting in severely impaired consolidation [63,64], Figure I.…”
Section: Offline Memory Replaymentioning
confidence: 99%
“…Importantly, this replay seems to coincide with the sharp wave ripples that originate in the hippocampus and are characteristic of SWS. These have been shown to be important for spatial learning in rats, with disruption of sharp wave ripples resulting in severely impaired consolidation [63,64], Figure I.…”
Section: Offline Memory Replaymentioning
confidence: 99%
“…Memory consolidation is thought to involve post-encoding reactivation of the activity patterns present during initial experience (activity replay) (Girardeau et al, 2009;Dupret et al, 2010). The frequency of activity replay decreases after the learning experience; replay is most frequent in the minutes following an experience (Tatsuno et al, 2006) but may persist for 18-24 h (Kudrimoti et al, 1999).…”
Section: Ic++ Silencing Of Creb-overexpressing Dg Neurons Shortly Aftmentioning
confidence: 99%
“…This result and other similar studies (Liu et al, 2012;Ramirez et al, 2013) identify neurons allocated to an engram. However, post-learning processes, presumably in neurons allocated to the engram, are thought to be important for successful memory consolidation (Marr, 1971;Buzsáki, 1989;Wilson and McNaughton, 1994;Girardeau et al, 2009;Ego-Stengel and Wilson, 2010;Carr et al, 2011). In vivo recording studies show that the precise patterns of event-induced neuronal activity may be subsequently replayed offline, during sleep (Skaggs and McNaughton, 1996;Ji and Wilson, 2007), or quiet wakeful periods (Carr et al, 2011).…”
Section: Inhibition Of a Dg Fear Engram Shortly After Training Disrupmentioning
confidence: 99%
“…More recently, cortical inhibitory networks have also been proposed to play a critical role in the generation of faster activities that include oscillations in the low (i.e, beta-gamma oscillations at 20-80 Hz) and high frequency range (>80 Hz, so called ripples) (Buzsáki et al, 1992). Interestingly, both beta-gamma rhythms and ripples occurring in cortical areas (Gray et al, 1989;Murthy and Fetz, 1992;Singer and Gray, 1995), including those of the limbic system Chrobak and Buzsáki, 1998;Csicsvari et al, 1999Csicsvari et al, , 2003, have been implicated in higher brain processes such as attention, sensorimotor integration, consciousness, learning and memory (Girardeau et al, 2009;Montgomery and Buzsáki, 2007). Therefore, it has been suggested that these oscillatory rhythms represent the basic neuronal processing state of the brain (Basar et al, 1999).…”
Section: Role Of Gaba a Receptors In Neuronal Network Oscillationsmentioning
confidence: 99%